2013
DOI: 10.1080/14783363.2011.637783
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of customer relationship management in hospital-based and privately run nursing homes in Taiwan

Abstract: This study evaluates the implementation of customer relationship management (CRM) in nursing homes in Taiwan. A total of 615 respondents from 30 hospital-based nursing homes and 108 privately run nursing homes in Taiwan are analysed. The results indicate that these two types of nursing homes emphasise different CRM activities to build positive relationships with their residents. Hospital-based nursing homes put more emphasis on understanding resident needs and providing prompt care service via knowledge learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The analyses indicated that there were strong relationships among the recognized factors throughout the model. This is in accord with References [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], who have theoretically hypothesized there are significant relationships between the strategic practices ( Table 2) and CRM results/success. Empirically, Yim et al [19] indicated these four critical dimensions significantly influence CRM results.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The analyses indicated that there were strong relationships among the recognized factors throughout the model. This is in accord with References [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], who have theoretically hypothesized there are significant relationships between the strategic practices ( Table 2) and CRM results/success. Empirically, Yim et al [19] indicated these four critical dimensions significantly influence CRM results.…”
Section: Discussionsupporting
confidence: 76%
“…According to the descriptive classification of Zablah et al [44], CRM is described in the available literature as a (1) process [18,19,21,30], aiming at establishing the relational flows and developing the process of creating and sustaining a fully profitable portfolio of relationships with the customers; (2) strategy [16,19,[21][22][23]25,[32][33][34]45], aiming at embedding the customer satisfaction-retention-loyalty chain to develop sustainable relationships with the customers that are (potentially) valuable; (3) philosophy [44], aiming at achieving customer centricity for the organizational sustainability; (4) capability [29], aiming at developing the organizational knowledge and capability to construct the sustainable relationships with the respective customers toward business excellence; and/or (5) technological tool [17,24], aiming at mingling marketing, sales, and knowledge-capable systems to create partnerships.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisational learning degree significantly and positively influences the degree of execution of CRM activities (Benavent & De La Villarmois, 2006;Chang & Ku, 2009). Different types of operational strategy significantly and differently influence the execution of CRM activities (Ko, Kim, Kim, & Woo, 2008;Wang, 2013). However, in empirical studies, few of them include market orientation, organisational learning and operational strategy in CRM activities to probe into their effect on operational performance.…”
Section: Introductionmentioning
confidence: 94%
“…The 25 years of evolution of TQM and related quality studies have been well summarised by Dahlgaard-Park, Chen, Jang, and Dahlgaard (2013). During the last two decades, TQM has been also expanded to non-manufacturing service sectors including higher education, health care, customer satisfaction, tourism, and recently, innovation (van Iwaarden & van der Valk, 2013;Wang, 2012;Xiaorong, Bojian, & Huili, 2012). Asif and Searcy (2014) argued that performance excellence in higher education institutions requires the management of the capabilities related to research, programme design and delivery, and service performance.…”
Section: Literature Review On National Standards Capabilitymentioning
confidence: 99%